Semi-analytical model for compressive arch action capacity of RC frame structures. (October 2020) - Azim, Iftikhar; Yang, Jian; Farjad Iqbal, Muhammad; Faisal Javed, Muhammad; Nazar, Sohaib; Wang, Feiliang; Liu, Qing-feng
Abstract: Compressive arch action (CAA) is one of the favorable resistance mechanisms at low deflections against progressive collapse of reinforced concrete (RC) frame buildings. In this study, Park & Gamble model for calculating the CAA capacity of RC frame structures is modified by incorporating a compressive stress block for high strength concrete (HSC). Meanwhile, a comprehensive database of RC specimens is collated and the modified model is applied on the database to determine the peak deflection ( δ ) values at CAA by using an iterative approach. The δ values obtained are then modelled by using distinctive features of gene expression programming (GEP) to develop a relationship for δ as a function of height ( h ) and net span length of the two beams after the column removal ( L ). The proposed model is validated against a wide range of published results and compared with other models available in literature. The comparison shows that the proposed modified Park & Gamble model can accurately predict the CAA capacity of the specimens. Moreover, the developed model is easy-to-use and skips the oversimplified assumption proposed in the Park & Gamble model to calculate δ (i.e. δ  = 0.5*depth of the specimen).